Labeled breath tests in patients with NASH: Octanoate oxidation relates best to measures of glucose metabolism - Mucinski, Justine M.; Perry, Alisha M.; Fordham, Talyia M.; Diaz-Arias, Alberto; Ibdah, Jamal A.; Rector, R. Scott; Parks, Elizabeth J. (Frontiers in Physiology, 2023)
In vivo methods to estimate human liver mitochondrial activity are lacking and this project’s goal was to use a noninvasive breath test to quantify complete mitochondrial fat oxidation and determine how test results changed when liver disease state was altered over time. Patients with suspected nonalcoholic fatty liver disease (NAFLD; 9 men, 16 women, 47±10 years, 113±23 kg) underwent a diagnostic liver biopsy and liver tissue was histologically scored by a pathologist using the NAFLD activity score (0-8). To assess liver oxidation activity, a labeled medium chain fatty acid was consumed orally (23.4 mg 13C4-octanoate) and breath samples collected over 135 min. Total CO2 production rates were measured using breath 13CO2 analysis by isotope ratio mass spectrometry. Fasting endogenous glucose production (EGP) was measured using an IV infusion of 13C6-glucose. At baseline, subjects oxidized 23.4±3.9% (14.9-31.5%) of the octanoate dose and octanoate oxidation (OctOx) was negatively correlated with fasting plasma glucose (r=-0.474, P=0.017) and EGP (r=-0.441, P=0.028). Twenty-two subjects returned for repeat tests 10.2±1.0 months later, following lifestyle treatment or standardized care. OctOx (% dose/kg) was significantly greater across all subjects (P=0.044), negatively related to reductions in EGP (r=-0.401, P=0.064), and tended to correlate with reduced fasting glucose (r=-0.371, P=0.090). Subjects exhibited reductions in steatosis (P=0.007) which tended to correlate with increased OctOx (% of dose/kg, r=-0.411, P=0.058). Based on our findings, the use of an 13C-octanoate breath test may be an indicator of hepatic steatosis and glucose metabolism, but these relationships require verification through larger studies in NAFLD populations.